2019
DOI: 10.1111/aas.13492
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative quality and safety using Efficacy Safety Score (ESS) and a wireless patient monitoring system at the ward: A randomised controlled study

Abstract: Background Postoperative pain, side‐effects and time to mobilisation are indicators for the quality of postoperative recovery. The aim of this randomised controlled study was to investigate if efficacy safety score (ESS) combined with a wireless patient monitoring system would improve these clinical outcomes for patients at a general surgical ward. Methods The trial included 195 patients randomised to a standard care group (SC‐Group) or intervention group (INT‐Group) receiving continuous wireless monitoring of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…As the authors provided the total number of discharges, the actual event numbers were calculated for inclusion in our analysis [26]. Similarly, another included study presented the hospital length of stay (LoS) in hours [27], this was converted to days for the analysis. In a further study, the authors presented LoS in median (Interquartile range, IQR), which was converted to mean (standard deviation, SD).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the authors provided the total number of discharges, the actual event numbers were calculated for inclusion in our analysis [26]. Similarly, another included study presented the hospital length of stay (LoS) in hours [27], this was converted to days for the analysis. In a further study, the authors presented LoS in median (Interquartile range, IQR), which was converted to mean (standard deviation, SD).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies also reported the patient American Society of Anaesthesiologists (ASA) score for preoperative functional status [42], with a median ASA score of 2 ("Patient has mild systemic disease") in three studies [29,30,43] and 3 ("Patient has severe systemic disease that is not incapacitating.") in one [27].…”
Section: Study Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations